Hematological Picture of Rabbits Immunized with Pseudomonas aeruginosa - Razook, Basil R.F.; Al-ani, Ahmed N .; Mahmood, Majid M. (The Iraqi Journal of Veterinary Medicine, 2020)
The current study was established to find out the role of immunization of Pseudomonas aeruginosa-whole sonicated antigen in adult white fur domestic rabbits. To achieve this goal, fifteen rabbits were allocated into 3 groups, the first group was immunized with P. aeruginosa–whole sonicated antigen and challenged with viable pathogenic P. aeruginosa; the second group (control negative) was treated with phosphate buffer saline and the third group was injected with viable pathogenic P. aeruginosa (control positive). The results demonstrated increasing levels of the measured parameters blood picture (total WBCs, lymphocytes, and granulocytes, RBCs and hemoglobin concentrations) in the first group compared with control negative group (T test was used). In contrast, a sharp fall was noted in total thrombocytes (platelets) count in the first group compared with control negative group. It can be concluded that immunization with P. aeruginosa– whole sonicated antigen may consider as a potent reproducible effective immunogen model for experimental immunological studies in rabbits.